Higher prevalence of wheezing and lower FEV1 and FVC percent predicted in adults with sickle cell anaemia: A cross‐sectional study. Issue 2 (22nd September 2016) - Musa, Baba M.; Galadanci, Najibah A.; Rodeghier, Mark; Debaun, Michael R.
ABSTRACT: Background and objective: Respiratory symptoms including wheezing are common in adults with sickle cell anaemia (SCA), even in the absence of asthma. However, the prevalence of spirometry changes and respiratory symptoms in adults with SCA is unknown. Methods: Using a cross‐sectional study design, we tested the hypothesis that adults with SCA (cases) would have higher rates of lower airway obstruction and wheezing than those without SCA (controls) using the American Thoracic Society Division of Lung Diseases' questionnaire. Patients were adults with SCA aged between 18 and 65 years. Controls were consecutive unselected individuals without SCA who presented to an outpatient general medicine clinic. Results: We enrolled 150 adults with SCA and 287 consecutive controls without SCA. The median age was 23.0 and 27.0 years for adults with and without SCA, respectively. Cases were more likely to report cough without a cold (35.0% vs 18.6%, P < 0.001), lower forced expiratory volume in 1 s (FEV1 ) % predicted (70.1% vs 82.1%, P = 0.001) and lower forced vital capacity (FVC) % predicted (67.4% vs 74.9%, P = 0.001) than controls. In the multivariable model, wheezing was significantly associated with SCA status (OR = 1.69, 95% CI = 1.08–2.65, P = 0.024). Similarly, FEV1 % predicted was significantly associated with SCA status and wheezing ( P = 0.001 for both). Conclusion: Adults with SCA experience a higher rate of wheezing and impaired respiratory functions compared with controls from the same region. Abstract : This study demonstrates that adults with sickle cell anaemia have higher prevalence of wheezing and lower FEV1 % and FVC% predicted than adults without sickle anaemia. Watch the video abstract